Fishery profiling and stock assessment of blue swimming crabs, Portunus pelagicus, in San Pedro Bay. - Montallana, Steffi Dominique S.; Tan, Irene L. (Steffi Dominique S. Montallana, 2018)
The blue crab fishing industry plays a major role in commercial fisheries in Region 8. This study assessed the crabber's profile and the wild stock status of blue swimming crab (BSC) fishery in Sitio Kataisan and Brgy. Payapay, San Jose, Tacloban City; and Brgy. San Roque, Tanauan, Leyte. There were 246 respondents and majority of the crabbers are male and married (99%). Fresh-caught crabs were distributed to different sectors and most of these crabs were sold to buying stations and consumers (28% for each sector). Monitoring of the BSC catch was done from July to November 2014 in the three sampling sites. Estimates of the catch and catch rates were made based on the monthly production, daily catch, and catch per unit effort. The estimated monthly production of BSC in the area showed an increasing trend from July to November. In this study, the Emax (maximum yield per recruit exploitation rates) for crab pots and gillnets in San Pedro Bay are 0.903 and 0.919, correspondingly. Also, results for the E-10 (present yield) values for crab pots and gillnets revealed 0.763 and 0.753, respectively. The standard E values are 0.38 and 0.393. However, the E values for both sexes using crab pots and gillnets were recorded as 0.54 and 0.55, respectively. The component of the stock assessment gives information on the values of the species parameter which, when compared to standard values, give the status of the resource. Since the values obtained for the exploitation rate (0.54 and 0.55) is higher than the standard E value (0.38 and 0.393), it may be concluded that the current status of the blue swimming crab population in San Pedro Bay is exploited beyond the optimum yield.